„Dlaczego będę to opowiadał”. Senny świat kobiet w Narracjach Władysława Słowackiego .......... 27 - Rzepniewska, Anna (Sny kobiet, sny o kobietach – od romantyzmu do Młodej Polski, 2020)
“WHY I WILL SAY IT”. THE DREAMY WORLD OF WOMEN IN NARRATIONS [NARRACJE] OF WŁADYSŁAW SŁOWACKIThe article concerns Narrations [Narracje] – the collection of ten short stories by Władysław Słowacki. Men and women live there in two separate worlds. However, the events are presented from the male perspective, which is why the reader receives a deformed picture of the world of women, functioning in a dream-like manner. The article shows the consequences of such separation between men and women: from demonizing a woman, taking her voice and agency, to usurping power over her life and justifying violence. The conclusion and the greatest paradox of these considerations is the observation that these underrated women give the narrator the only motivation to tell a story in a stagnant reality.